An Analysis of Students’ Anxiety in Speaking English at First Grade of SMK Nasional - Julian Chandra; M Saleh Yahya Himni (Asshika: Journal of English Language Teaching and Learning, 2024)
The objective of this study was to identify the factors contributing to students' nervousness when speaking English and to assess their English speaking proficiency at SMK Nasional 2 Kayu Tanam. This research employs qualitative methodologies with a descriptive orientation. Two instruments were utilized in this research, specifically the LFCAS questionnaire developed by Horwitz in 1986 and the speaking test created by Brown in 2004. The research sample comprised 35 students, divided across two classes: class X accounting and class X TSM 2. The sample was obtained using purposive sampling. The research data was gathered through the administration of a questionnaire and a speaking test in two classes: class X accounting and class X TSM 2 SMK Nasional 2 Kayu Tanam. The results of the LFCAS questionnaire indicated that communication apprehension was at 33.5%, fear of negative evaluation at 24.56%, and test anxiety at 41.94%. The outcomes of the class X accounting and X TSM 2 in the five aspects are as follows: vocabulary 19.93%, grammar 19.26%, fluency 19.77%, pronunciation 20.6%, and understanding 20.44%. Based on the LFCAS questionnaire, pupils can be classified as either low or below average, whereas the results of the students' speaking test are classified as excellent.